ANALISIS PENGARUH JUMLAH KREDIT, LOAN TO ASSET RATIO (LAR), DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP NON-PERFORMING LOAN DI PT BANK RAKYAT INDONESIA (PERSERO) Tbk CABANG WONOGIRI TAHUN 2018 - Yuan Sasmita Nugraha; Burhanudin AY; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2019)
This study aims to determine the effect of the amount of credit, LAR, and LDR on Non-Performing Loans at PT Bank Rakyat Indonesia (Persero) Tbk Wonogiri. This study used quantitative research methods. The data sources used in this study are secondary data, namely the financial statements of PT Bank Rakyat Indonesia (Persero) Tbk, the Wonogiri Branch Office in 2018. Data collection methods in this research were documentation and literature studies. This study used classical assumption test techniques, multiple linear regression analysis, and hypothesis testing (t test, f test, coefficient of determination). The results of data analysis are: The amount of credit has a positive and significant affect on the NPL, Loan To Asset Ratio (LAR) has negative and significant affect on the Non-Performing Loan (NPL), Loan To Deposit Ratio (LDR) has positive and significant affect on the Non-Performing Loan (NPL). Keywords: Amount of Credit, LAR, LDR, NPL.